Analisis Kinerja Guru dalam Melaksanakan Proses Pembelajaran pada Siswa SDN 1 Sambongbangi - Maesaroh, Siti, Murfiah Dewi Wulandari, S.Psi.,M.Psi Psikolog (2017)
The purpose of this study are: (1) to analyze the performance of teachers in implementing the learning process at SDN 1 Sambongbangi. (2) to know constraints faced in teacher performance in implementing learning process to student, (3) knowing solution in overcoming obstacle faced in teacher performance in implementing learning process to student. This type of research is qualitative. The design of this study is a case study. The data analysis technique uses source triangulation. The results of this study are: (1) the performance of less professional teachers such as not preparing the RPP and often entering late in working hours (2) the teacher performance constraint is the process of learning is not comfortable due to classroom conditions that need repaired, Less innovative learning and often late entry, (3) teacher performance solutions that are the first teachers provide motivation, positive encouragement, and guide students patiently to understand learning. And teachers encourage students to continue learning in any condition, just like the classrooms that need to be improved. Secondly, teachers should attend several trainings to improve the teacher's professional aspect. Keywords: Teacher Performance, Learning, Student